Hubungan Status Gizi Dan Aktivitas Olahraga Dengan Kejadian Sindrom Pramenstruasi Pada Santriwati Di Pondok Pesantren Darul Huda Sipungguk Tahun 2022 - Lubis, Dumasari; Syarif Hamidi, M. Nizar; Syahda, Syukrianti (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Premenstrual syndrome occurs more often in Asian countries than in Western countries. According to Indonesian Health Research, in Indonesia, it was found that 95% of teenagers have at least one premenstrual symptom syndrome. The aim of this research is to analyze the relationship between nutritional status and sports activities with the incidence of premenstrual syndrome in female students at the Darul Huda Sipungguk Islamic Boarding School in 2022. This research design uses a quantitative design with a cross sectional research design. The population in this study was 86 female students. The sample in this study was 86 female students. The data analysis used in this research is Univariate Analysis and Bivariate Analysis. From the results of research using univariate analysis, it was found that the majority of nutritional status was at normal nutritional status, as many as 47 female students (54.6%). Some of the respondents who did non-routine sports activities were 48 female students (55.8%). some of the respondents experienced premenstrual syndrome as many as 60 female students (69.8). Meanwhile, in the bivariate analysis, the results showed that there was a relationship between nutritional status and sports activity with the incidence of premenstrual syndrome in female students at the Darul Huda Sipungguk Islamic Boarding School in 2022. The results of this research are expected to provide theoretical input and add to the results of scientific information related to the incidence of premenstrual syndrome. especially for female students at the Darul Huda Islamic Boarding School